Karakter Performa Pertumbuhan Ayam Daging (Gallus domesticus) yang disuplementasi Debris Daluga (Cyrtosperma merkusii) - Emma Mauren Moko; Reffie Wullus; Rudi Alexander Repi; Livana Dethris Rawung; Dino Rahardiyan; Johanna Zusye Wantania; Mercy Maggy Franky Rampengan (Universitas Sam Ratulangi, 2024)
In order to enhance the growth of gallus domesticus broiler chickens, sythetic and natural supplemantion are commonly added to the feed. This study was conducted to understand the impact of adding daluga (Cyrtosperma merkusii) starch processing debris (residuals) as supplements to the current feed towards the growth performances of the broilers. 60 one day old unisexed broiler Chickens were used in this study. The experiments carried out was conducted with a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Feeding regiments were arranged with supplements of 0%, 0,065%, 0,13%, and 0,26% daluga debris. Observation was conducted for 45 days, and records of weight gain, final weight, cumulative consumption, and feed conversions were taken weekly. Results indicated that daluga debris supplementation (p<0,05) significantly effected the growth performances. Supplementation at 0,065% appeared to show the most optimum performance